THE ROLE AND IMPORTANCE OF DIGITAL TECHNOLOGY IN EDUCATION SOX - Egamov Sultonjon Malikovich; Arzikulov Fazliddin; Isroilov Ulug’bek (Journals Park Publishing, 2025)
This article cites the necessary information about the tasks of students in the educational process that should be used in order to develop digital technology. The article describes digital technology, virtual reality, the use of digital technology in education, the advantages of digital technology in educational system Vosti.
Keywords: Education, digital technology, digital technology in education, ICT, higher education system, modern education, Internet system, virtual reality.